BBC boss says disinformation ‘trust crisis’ putting social fabric of UK at risk - Savage, Michael (The Guardian, 2025)
Britain’s status as a cohesive, democratic society is at risk for the first time in a generation as the rise of social media platforms and disinformation fuel a “trust crisis”, the BBC’s director general has said. In a wide-ranging address about the future of the corporation, Tim Davie said BBC News would start to make special content for platforms such as YouTube and TikTok, where disinformation can go unchecked, as he couched the broadcaster as a “precious national asset” preventing the UK from becoming a society in which there were no shared facts.
Keywords: BBC; BBC licence fee; Culture; Digital media; Media; Social media; TV news; Television; The news on TV; Tim Davie